2011
DOI: 10.1089/neu.2010.1561
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Serum Biomarker Levels after Blast Traumatic Brain Injury

Abstract: Neuronal and glial proteins detected in the peripheral circulating blood after injury can reflect the extent of the damage caused by blast traumatic brain injury (bTBI). The temporal pattern of their serum levels can further predict the severity and outcome of the injury. As part of characterizing a large-animal model of bTBI, we determined the changes in the serum levels of S100B, neuron-specific enolase (NSE), myelin basic protein (MBP), and neurofilament heavy chain (NF-H). Blood samples were obtained prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 33 publications
9
72
5
1
Order By: Relevance
“…Elevated serum MBP levels are indicator of white matter tract and also axonal injury [34]. In this study, we observed a time-dependent increase of serum MBP levels reaching maximum at the termination of the experiment (day 14).…”
Section: Axonal Injurysupporting
confidence: 60%
See 1 more Smart Citation
“…Elevated serum MBP levels are indicator of white matter tract and also axonal injury [34]. In this study, we observed a time-dependent increase of serum MBP levels reaching maximum at the termination of the experiment (day 14).…”
Section: Axonal Injurysupporting
confidence: 60%
“…It was 7 days after subarachnoid hemorrhage [33], 3 days after spinal cord injury [7], 2-3 days following CCI [11] and 6h following blast TBI [34]. In this study highest serum NF levels were detected at day 1 and 14.…”
Section: Axonal Injurysupporting
confidence: 44%
“…Berger et al (2010) reported that the detection of S100B and MBP serum concentrations is important for predicting prognosis, and that MBP had an accuracy of 73% and specificity of 61%, and S100B had a sensitivity of 59% and specificity of 100%. Gyorgy et al (2011) also demonstrated that higher S100B and MBP serum levels indicated poorer prognosis. Our results showed that the MBP serum level of preterm infants with cerebral white damage, at 1 day after birth, was not significantly different from that of normal preterm infants.…”
Section: Discussionmentioning
confidence: 87%
“…S100B cannot penetrate the blood-brain barrier in the normal condition; however, when neuroglial cells undergo necrosis, S100B is leaked and penetrates across the injured blood-brain barrier, increasing its level in serum (Chen et al, 2008). The serum S100B level reflects the degree of damage, and is useful in the evaluation of the therapeutic efficiency of drugs and of the prognosis of the central nervous system (Fishler et al, 1965;Egberts et al, 2008;Murabayashi et al, 2008;Berger et al, 2010;Gyorgy et al, 2011). In this study, the results showed that the S100B level of preterm infants with cerebral white damage 1 day after birth had no significant difference with that of normal preterm infants, and that S100B concentration increased on the 3rd day and peaked on the 7th day; however, with the improvement of body condition, there was an obvious decrease on the 14th day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation